Evaluating the impact of remittances on human capital investment in the Kyrgyz Republic - Gao, Xin (Metro Manila, Philippines Asian Development Bank, 2021)
This study uses a 5 year panel dataset to explore the impact of remittances on educational achievement. It identifies increased expenditure on durable goods and extended hours of farm labor by children among recipient households. The findings call for actions that mitigate the negative effects and incentivize families to spend remittances on education.
Keywords: Social rights -- Developing countries; Economics; Electronic books